Porphine Homocoupling on Au(111) - Seufert, Knud; McBride, Fiona; Jaekel, Simon; Wit, Bareld; Haq, Samreen; Steiner, Alexander; Poli, Paolo; Persson, Mats; Raval, Rasmita; Grill, Leonhard (Journal of Physical Chemistry C, 2019)
The covalent coupling of porphine molecules on Au(111) is studied by scanning probe microscopy experiments and density functional theory. At sufficient temperatures, dehydrogenative C-C coupling of the un-functionalized molecules occurs directly on the surface. Characteristic dimer structures between individual porphine molecules are observed and assigned to various binding motifs that are distinguished by specific intermolecular connections. Different preparations show that the relative abundance of these motifs depends on the temperature of the gold sample during deposition and is explained by calculated free energies and kinetic aspects that are relevant during the linking process. Observations on the gold terraces are completed by studying polymerization at step edges, giving insight into their role during the covalent linking process.